2016
DOI: 10.1002/advs.201500434
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent Metal–Organic Frameworks for Gas Sensing

Abstract: Luminescence of porous coordination polymers (PCPs) or metal–organic frameworks (MOFs) is sensitive to the type and concentration of chemical species in the surrounding environment, because these materials combine the advantages of the highly regular porous structures and various luminescence mechanisms, as well as diversified host‐guest interactions. In the past few years, luminescent MOFs have attracted more and more attention for chemical sensing of gas‐phase analytes, including common gases and vapors of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(131 citation statements)
references
References 152 publications
(264 reference statements)
2
127
0
2
Order By: Relevance
“…Over the past three decades, MOFs have been paid much attention for their great potential applications in many areas [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, MOFs have been paid much attention for their great potential applications in many areas [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…The collaborative functionalities of the intrinsic porosity and luminescent properties of MOFs make them very promising as a new type of sensory material . The porous, crystalline MOF architecture provides several advantages .…”
Section: Functionalization Of Mofs For Photoluminescent Tuning and Sementioning
confidence: 99%
“…In the past few years, some luminescent MOFs have also been explored for sensing gas‐phase analytes, including common gases and vapors of solids/liquids …”
Section: Functionalization Of Mofs For Photoluminescent Tuning and Sementioning
confidence: 99%
“…[21] When the well-oriented MOF thin films adsorbed analytes, in most cases, the changes in structural, electrical, or optical properties, such as fluorescence, refractive index, or color can be detected. [23,24] Xu et al [25] reported that the HKUST-1 that loaded on mass-gravimetric resonant cantilevers exhibited high sensitivity to p-xylene with the detection limit of 400 ppb. While for Cu-based MOF, Cu(bdc)·xH 2 O was grown as a thin film on interdigitated electrodes, generates capacitance change upon acetone, ethanol, toluene, and methanol vapor, and exhibits more sensitivities at low concentrations for toluene.…”
Section: Introductionmentioning
confidence: 99%